Effects of warming, grazing/cutting and nitrogen fertilization on greenhouse gas fluxes during growing seasons in an alpine meadow on the Tibetan Plateau - Zhu, Xiaoxue; Luo, Caiyun; Wang, Shiping; Zhang, Zhenhua; Cui, Shujuan; Bao, Xiaoying; Jiang, Lili; Li, Yaoming; Li, Xine; Wang, Qi; Zhou, Yang (Agricultural and forest meteorology, 2015)
•Warming significantly increased carbon dioxide emissions in drought years.•Warming significantly increased methane uptake.•Winter clipping did not significantly affect nitrous oxide emissions.•Nitrogen fertilization significantly increased methane uptake in drought years. Increased nitrogen (N) deposition within the context of both warming and grazing is relevant to understand the response of greenhouse gases fluxes (GHG) (i.e. CO2, CH4 and N2O fluxes) for alpine meadow ecosystems to projected changes in the environment. A previous controlled warming and grazing experiment only included no warming with no grazing (NWNG), no warming with grazing (NWG), warming with no grazing (WNG) and warming with grazing (WG) from 2006 to 2010. N fertilization was added to the experimental setup to determine the effects of warming, grazing and N fertilization on GHG fluxes in an alpine meadow on the Tibetan Plateau during the growing seasons from 2010 to 2012. Sheep grazing was utilized during the growing season from 2006 to 2010 and cutting was used as simulation of grazing during the non-growing seasons in 2011 and 2012. Warming significantly increased average seasonal CO2 emission by 10%, and nitrogen addition increased average seasonal CH4 uptake by 14% during the growing seasons in the dry years of 2011 and 2012. Warming increased average seasonal CH4 uptake by 32–46% over the 3-year period, and grazing increased annual average N2O emission by 62% only in 2010. N fertilization alone did not significantly affect CO2 and N2O fluxes during the experimental period. The interactive effects of warming, grazing/cutting and N fertilization effect on daily CH4 or daily N2O flux depended on sampling date. Ecosystem CO2 emission was mainly affected by soil temperature and plant aboveground net primary production (ANPP), which explained about 55% and 18% of its variation. Soil moisture and ANPP could explain 17% and 8% of the variation of CH4 uptake in the region. Our results suggest that the stimulating effect of warming on ecosystem respiration still occurs in 2011 and 2012 after warming for seven years. Moreover, our results imply that moderate grazing/cutting may be preferred compared with no grazing or no cutting because its negative effect on GHG fluxes was small, and interactive effect of warming, grazing/cutting and increased N deposition on GHG emission could be neglected in the alpine meadow.